Development of a simple equivalent tornado wind profile for structural design and evaluation. Issue 213 (June 2021) - Huang, Q.; Jiang, W.J.; Hong, H.P.
Abstract: Tornadoes cause damage to buildings and infrastructure. Providing the spatially varying tornado activities or tornado occurrence rate alone does not facilitate the tasks of checking and evaluating structures subjected to the tornado wind velocity hazard. In the present study, the estimation of the quantile of the tornado wind velocity hazard along the height for southern Ontario – a tornado-prone region in Canada – is carried out. For the assessment, a tornado occurrence rate model is developed by considering the reporting bias due to population density and by using the cloud-to-ground lightning flash density and thunderstorm days per year as the explanatory variables. Also, a simple equivalent along height tornado design wind profile for a vertical line-like structure is proposed by considering the bending moment and shear force along the height of the structure. Moreover, the concept of disaggregation analysis is employed to identify the scenario tornado wind profiles. The results indicate that the identified scenario wind profiles could be crudely bounded by using the rectangular wind profile and the power-law wind profile for synoptic winds, which are all hinged at the return period value of the tornado wind velocity at 10 ​m height. Highlights: A systematic modeling of tornado occurrence for southern Ontario is presented. The cloud-to-ground lightning flash density and thunderstorm days are used as explanatory variables. Tornado wind profile based on quantiles of tornado wind speed is presented. Simple equivalent tornado design wind profiles are developed or point-like and line like structures.